Pemahaman ‘Itāb Halus dan ‘Itāb Tegas Perspektif Al-Qur’an terhadap Komunikasi Interpersonal: Tinjauan Psikologis - Zakariah, Abdul Haris Nasution; Syam, Nurfadhilah; Mukmin, Mukmin (LP2M IAIM Sinjai, 2024)
Abstract This journal discusses several verses from the Koran which explain the morals of the Prophet Muhammad saw. The verse in question is known as the 'Itāb verse or verses about reprimand. Research into the verse 'Itāb provides information about the warning to the Prophet Muhammad. which is based on the perspective of the Koran and is also able to provide an overview to Muslims of the purpose of these verses. This research uses qualitative research. The research results concluded that these verses are generally divided into two forms of 'Itāb, namely: 'Itāb is subtle and 'Itāb is firm. Which will show the level of warning given by the Prophet Muhammad saw. and the object of the rebuke which displays the material object of God's rebuke.